no equation to simplify because there is no equal sign.
Splitting the equation up into the two variables: x + 4x = 5x -7y + -2y = -9y Therefore, the simplified version is: 5x - 9y
To do this equation, you collect like terms. 7x-4x+x-15 is your original equation, you have 3 terms with "'x'" in them, and they are 7x, -4x, and x. 7x + (-4x) +x simplifies to 4x, because 7-4 = 3 + 1 = 4 (the x is really 1x....). After this, you get 4x-15, which is as simplified as this equation can be.
Yes, it can be simplified into 4x.
The expression ( 52 - 4x - 4 ) can be simplified by combining like terms. First, subtract 4 from 52, which gives you ( 48 - 4x ). So, the simplified form of the expression is ( 48 - 4x ).
Without an equality sign and not knowing the plus or minus values of some of the given terms the given expression can't be considered to be an equation.
Splitting the equation up into the two variables: x + 4x = 5x -7y + -2y = -9y Therefore, the simplified version is: 5x - 9y
To do this equation, you collect like terms. 7x-4x+x-15 is your original equation, you have 3 terms with "'x'" in them, and they are 7x, -4x, and x. 7x + (-4x) +x simplifies to 4x, because 7-4 = 3 + 1 = 4 (the x is really 1x....). After this, you get 4x-15, which is as simplified as this equation can be.
Without an equality sign it's not an equation but it can be simplified to: 7x-5
The equation can be written as y = 16x/20 which can be simplified to y = 4x/5
Lets simplify the above given equation : -8 plus 6(-x - 3) plus 4x simplified as : -8-6x -18 +4x =-2x -26 . =-2(x+13).
It has no solution and if you mean 4x+10+3x+40-3x then it can be simplified to: 50+4x _________________________________________________________________________________________ Assuming that the equation is 4x+10+3x+40-3x = 0, then it will reduces to 4x = - 50, then the answer is: x = -12.5
There is no equation, only an expression. An expression can be simplified but cannot be solved.
None because without an equality sign it is not an equation but the given expression of 4x-22(2x-1) can be simplified to: 22-40x
None because without an equality sign it is not an equation but the given expression of 4x-22(2x-1) can be simplified to: 22-40x
4x + 6 = 6x - 12-4x -4x6 = 2x - 12+12 +1218 = 2xx=9
14
If you mean: -8y-(x-4x)+3y then it is 3x-5y simplified